2018
DOI: 10.11609/jott.4039.10.8.12008-12017
|View full text |Cite
|
Sign up to set email alerts
|

<b>Camera-trapping survey to assess diversity, distribution and photographic capture rate of terrestrial mammals in the aftermath of the ethnopolitical conflict in Manas National Park, Assam, India</b>

Abstract: Information on the presence and distribution of species is crucial for conservation planning and management within a region. Documentation of species assemblages in Manas National Park (MNP) in the aftermath of conflict is critical for informed conservation interventions. For nearly two decades , conservation efforts in MNP were compromised by ethno−political conflict. We conducted camera trapping surveys of terrestrial mammals across three administrative forest ranges (Panbari, Bansbari and Bhuyanpara) of MNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
0
19
1
Order By: Relevance
“…The previous camera-trapping studies in Manas National Park provides information on relative abundances of tigers and their prey [52], carnivore diversity [53], and density estimation of carnivores and herbivores [40]. Recently, Borah et al [54] provide info on density estimation of common leopard and clouded leopard; whereas Lahkar et al [55] explained about diversity, distribution and photo-capture rate of mammals of MNP. In the present study, we examine activity rhythms and the lunar cycle effect on the mammalian fauna in the semi-evergreen forest of Manas National Park.…”
Section: Discussionmentioning
confidence: 99%
“…The previous camera-trapping studies in Manas National Park provides information on relative abundances of tigers and their prey [52], carnivore diversity [53], and density estimation of carnivores and herbivores [40]. Recently, Borah et al [54] provide info on density estimation of common leopard and clouded leopard; whereas Lahkar et al [55] explained about diversity, distribution and photo-capture rate of mammals of MNP. In the present study, we examine activity rhythms and the lunar cycle effect on the mammalian fauna in the semi-evergreen forest of Manas National Park.…”
Section: Discussionmentioning
confidence: 99%
“…To the south are 136 villages (within 3 km of its boundary) and to the north, it is contiguous with the Royal Manas National Park (RMNP), Bhutan. Comprising of Eastern Wet Alluvial Grasslands, Moist Deciduous and Semi‐Evergreen forests (Champion & Seth, 1968), the park supports a diverse assemblage of fauna despite a history of ethnopolitical conflicts in the region (Lahkar et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…MNP is a site where prey densities are not limiting, yet anthropogenic influences alter the spatial and temporal behaviour of prey (Lahkar et al ., 2020). Situated in a region that has experienced armed ethnopolitical conflict from the late 1980s until 2003, studies show that populations of several species were depressed, but are now recovering (DebRoy, 1991; Goswami & Ganesh, 2011, 2014; Lahkar et al ., 2018). More specifically, parts of MNP that have remained conflict‐free since 2003 (Bansbari‐Bhuyanpara ranges) have significantly higher photo‐capture rates of ungulates than an area that experienced conflict until 2016 (Panbari range) (Lahkar et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MNP is an 850 km 2 protected area along the Indo-Bhutan international border (see Lahkar et al, (2020) (Olson et al 2001), where the observed frequency of melanism is five-fold higher than the expected number based on the global average (da Silva et al 2017). Since the end of ethnopolitical conflict in the region in 2003, MNP has received much biodiversity research and conservation attention (Borah et al 2014;Lahkar et al 2018Lahkar et al , 2020).…”
Section: Study Areamentioning
confidence: 99%